Analysis Of The Regulation Of The Rights Of Substitute Heirs According To Statutory Regulations And Legal Principles - Jamil, Sukran (CV. Inara, 2024)
The deceased heir can be replaced by his heir (his child) as a substitute heir. In legal terms, the legal norms governing substitute heirs contain legal dualism because they are regulated by more than one legal norm, namely the Civil Code and the KHI. The problem analyzed in this study is about the distribution of inheritance for substitute heirs based on a legal theory approach. The research method used to analyze the problem is the normative legal research method with a statutory regulatory approach and legal theory. The results of the study indicate that in Indonesia there is a dualism of legal norms governing inheritance including substitute heirs. Based on legal theory, the KHI applies to heirs who are Muslim because of its special nature according to Islamic law and for those outside Islam, the Civil Code can be used.